Conhecimento especializado de Geometria do professor do ensino fundamental I - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2019)
This research aimed to analyze the specialized knowledge ing Geometry of the Elementary School teacher, which works in public schools in the city of Telemaco Borba in the state of Paraná. It is a proposal according to the definitions and categorizations of the basic knowledge of the teaching practice proposed by Lee Shulman (1986, 1987), Grossman (1990), Ball, Thames and Phelps (2008), Carrillo et al. (2014) and Van Hiele Theory (2009). The research had as the object of study the specialized knowledge in mathematics (MTSK) – in particular the Geometry of the polyvalent teacher – acquired during the initial and continuous formation. Regarding this research methodology, was choose the qualitative approach of the case study type, according to the descriptive perspective. The instruments used for data collection were the exploratory questionnaire, activities to diagnose the mathematical knowledge of the students, a self-assessment questionnaire about the contents of Geometry proposed at the BNCC (2017), a questionnaire adapted from the CoRe proposed by Loughran, Mulhall, and Berry (2004) to capture teachers's PCK, and the field diary that depicted the relevant situations observed during data collection. Data analysis was performed using the Discursive Textual Analysis methodology, developed by Moraes and Galiazzi (2007). The results of the data analysis pointed to the fragility in the specific knowledge of Geometry, which influences the pedagogical knowledge of the theme. Another fact observed in this research was the deficit and/or lack of instruction in Mathematics, specifically on the topic of Geometry for multipurpose teachers.
Keywords: Conhecimento especializado de geometria; Ensino fundamental I; Ensino de geometria; Formação de professores; Professores polivalentes; Specialized knowledge of geometry; Elementary education; Geometry teaching; Teacher training; Polyvalent teachers; CNPQ::CIENCIAS EXATAS E DA TERRA::MATEMATICA